2019
DOI: 10.3389/fcimb.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Is a Defense Mechanism Inhibiting Invasion and Inflammation During High-Virulent Haemophilus parasuis Infection in PK-15 Cells

Abstract: Bacterial infections activate autophagy and autophagy restricts pathogens such as Haemophilus parasuis through specific mechanisms. Autophagy is associated with the pathogenesis of H. parasuis . However, the mechanisms have not been clarified. Here, we monitored autophagy processes using confocal microscopy, western blot, and transmission electron microscopy (TEM) and found that H. parasuis SH0165 (high-virulent strain) but not HN0001 (non-vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“… 48 Previous studies on ATG16L1 silencing have demonstrated that the subsequent disruptive autophagy is associated with an elevated production of the important pro-inflammatory cytokine IL-8 in epithelial cells exposed to Shigella and Haemophilus parasuis SH0165. 24, 25 We demonstrated that while H. pylori induced IL-8 production in PBMCs, this was not affected by ATG16L1 rs2241880 status. In contrast, IL-8 production was significantly enhanced in GC cells harboring the GG-genotype.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“… 48 Previous studies on ATG16L1 silencing have demonstrated that the subsequent disruptive autophagy is associated with an elevated production of the important pro-inflammatory cytokine IL-8 in epithelial cells exposed to Shigella and Haemophilus parasuis SH0165. 24, 25 We demonstrated that while H. pylori induced IL-8 production in PBMCs, this was not affected by ATG16L1 rs2241880 status. In contrast, IL-8 production was significantly enhanced in GC cells harboring the GG-genotype.…”
Section: Discussionmentioning
confidence: 72%
“…The above findings were mostly corroborated at the protein level ( Figure 5(b )) and support the notion that disruptive autophagy promotes an increased IL-8 response in epithelial cells upon infection. 24 , 25
Figure 5. ATG16L1 rs2241880 status does not affect IL-8 production in immune cells but modulates IL-8 and TNF-α production in AGS cells upon infection with Helicobacter pylori .
…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies demonstrated that autophagy could be triggered during microbial infection, such as bacteria, viruses, protozoa, and parasitic helminths [ 20 23 ]. However, autophagy induction has not been confirmed in Trichinella infection.…”
Section: Discussionmentioning
confidence: 99%
“…TEM experiments were conducted as the previous studies [19,34]. Samples were immersed in 1% osmium tetraoxide in PBS for 2h and then dehydrated in graded ethanol, and embedded in epoxy resin.…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%